Asian Pacific Lesbians and Gays (A/PLG) records. - ONE National Gay & Lesbian Archives ([Place of publication not identified] : [publisher not identified], 1977)
The materials in Asian Pacific Lesbians and Gays (A/PLG) Records comprise one of sixteen collections of records from the ONE National Gay and Lesbian Archives, the world's largest repository of LGBTQ materials. These files document the lives of LGBTQ individuals from 1940 to 2012, the organizations they founded, the discrimination they faced, and the devastation of the AIDS crisis. Most of the items concern individuals or groups from California. Founded in 1980 to address the needs of gay people of Asian and Pacific heritage, A/PLG strives to provide its members with social and educational programming. In 1997, A/PLG was renamed Asian/Pacific Gays and Friends. The materials in this collection include newsletters, distribution records, meeting files, membership records, photographs, correspondence, receipt books, and promotional materials, spanning the years 1977 to 2012. This collection is vital for anyone researching the many facets of LGBTQ life in California and the United States in the second half of the twentieth century.
Date range of documents: 1977-2002.
Reproduction of the orignals from the ONE National Gay and Lesbian Archives.
Keywords: Asian/Pacific Lesbians and Gays; Asian American gays; Pacific Islander American gays; Gay community -- California